E-Marketing Model for successful entrepreneurs - Zafar, Fareeha; Ahmad, Hafiz Sabih; Taha, Syed Muhammad (Advances in Social Sciences Research Journal, 2017)
This paper illustrates a new electronic model for successful entrepreneurs. The authors have analyzed classical models namely 5ls Model, 10 C’s of Marketing, 3-Race Planning, 4 C’s marketing model & McKinsey’s consumer decision journey, and have found certain inadequacy to fulfill the need of digital era in view of which the proposed model includes certain Tools, a Tranquil design, Contingency , Commitment level and feedback. This eventually helps in optimum utilization of electronic marketing tools. The proposed model is equally beneficial for Small scale and large scale businesses in order to gain visible growth and development which ultimately affect the economy of the state or country. This model helps entrepreneurs to flourish their business in a quick and enhanced way. The new design is comprehensive and brief; it fulfills the requirement of all types of trades which is comprehended in the paper.